Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan di SMK Marhas Margahayu - Deti Rostini; Wiwik Dyah Aryani; Rismawan Rismawan; Ida Rukhaida; Rivatul Mahmudah (Journal on Education, 2023)
Curriculum management is one of the aspects that influence the success of learning in national education. In addition, the curriculum is a learning program system to achieve institutional goals in educational institutions, so that the curriculum plays an important role in creating quality of schools. The approach used in this research is a qualitative approach with descriptive research, in which the researcher departs from the field to make intensive observations. Data collection methods are carried out through observation, interviews and documentation. To analyze the data, the writer uses descriptive qualitative analysis, namely describing and interpreting existing data to describe reality according to the actual phenomenon. The results of this study are that the SMK Marhas Margahayu in improving the quality of education has carried out Planning, Implementation and Evaluation. As a guiding tool in carrying out activities in the school environment.